Pupil response to accommodation and convergence in children and adolescents with accommodative disorders (Ukrainian Journal of Ophthalmology, 2025)
Background: As there is close association between pupil response and accommodation during gaze fixation on an object at any distance, it seems interesting to study pupil response to accommodation in patients with accommodative disorders.Purpose: To assess pupil response to accommodation and convergence in children and adolescents with accommodative disorders who varied in age and autonomic nervous system (ANS) tone.Material and Methods: One hundred and thirty children and adolescents (260 eyes) having accommodation spasm (AS) and 59 (118 eyes) having accommodative insufficiency (AI) were included in the study. They underwent measurements of best-corrected visual acuity, refractive errors, and axial length, and assessment of accommodation reserve (by the technique of Dashevsky) and body’s autonomic nervous system (ANS) balance (by Kerdo index). Pupillography studies were performed using an OK-2 pupillographer (Ukraine) to assess pupil area, amplitude of change in pupil area, and durations of phases of changes in pupil area.Results: An increased parasympathetic tone was more common among 6-14-year-old children with AS than among age-matched healthy children (64.5% vs 29-43%), and the rest of these cases had an increased sympathetic tone. The mean maximum pupil area Smax value for children with AS and increased sympathetic tone was 27.5 ± 4.1 mm2, which was 25.6% greater than for those with AS and increased parasympathetic tone (21.9 ± 5.6 mm2, p < 0.001), and 102% less than for healthy children with increased sympathetic tone (55.6 ± 13.5 mm2, p < 0.001). In addition, pupil constriction latency (Phase II) and active pupil constriction (Phase III) were longer for patients than for controls. Among children and adolescents with AS, pupil parameters significantly depended on the ANS tone, but not on the age. This was different from healthy children, in whom pupil area parameters correlated both with age and with ANS tone, whereas durations of changes in pupil area (i.e., phases III, V and VI) were correlated only with age. All children with AI had an increased sympathetic tone. Compared to healthy children with an increased sympathetic tone, children with AI demonstrated smaller Smax and longer pupil re-dilation latency (Phase V) (p < 0.05). There was no significant difference in other pupil characteristics between patients of the study and healthy individuals. We found a substantial difference in Smax between children with AS (23.94±5.5 mm2) and those with AI (49.3 ± 13.8 mm2).Conclusion: Children with AS develop some imbalance of the body’s and ocular autonomic nervous systems with a shift towards an increased parasympathetic activity. The relationships developed between pupil responses, age and state of autonomic innervation in children with AS are different from those in healthy children, with the tone of the ANS, but not age playing a major role. We found a substantial difference in Smax between children with AS and those with AI, which may be considered along with clinical signs and body’s ANS tone as differential diagnostic criteria for accommodative disorder and facilitate a pathogenesis-oriented treatment approach.
Keywords: accommodation spasm; accommodative insufficiency; pupillography; pupil response to accommodation and convergence; children and adolescents; autonomic nervous system